극수 및 부하의 크기 변화에 따른 유도전동기의 역률 보상 - 김종겸(Jong-Gyeum Kim); 김일중(Il-Jung Kim) (전기학회 논문지 P권, 68(1), 2019)
Induction motors are a typical inductive load. Since the inductive load has a low power factor, it is necessary to compensate the power factor so that it can be maintained above a certain level. To raise the power factor beyond a certain level, a capacitive load capacitor is used. An induction motor is presented with a capacitor capacity for power factor compensation based on voltage and output. In fact, the power factor of the induction motor varies slightly depending on the number of poles, and also depending on the increase or decrease of the load. This paper presents a method for selecting the optimum capacitor for the power factor which depends on the variation of the load and the poles in the same output motor. KCI Citation Count: 0